2006
DOI: 10.1177/0278364906064566
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Natural Dynamics to Reduce Energy Consumption by Controlling the Compliance of Soft Actuators

Abstract: Exploiting natural dynamics for bipedal locomotion, or passive walking, is gaining interest because of its energy efficiency. However, the natural trajectories of a passive walker are fixed during the design, thus limiting its mobility. A possible solution to this problem is creating a "semi-passive walker" equipped with actuators with adaptable compliance, which allows the natural dynamics to be changed according to the situation. This paper proposes a compliance controller, a strategy for continuously changi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
107
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(107 citation statements)
references
References 14 publications
0
107
0
Order By: Relevance
“…The optimisation of the passive system properties has also been discussed under more dynamic conditions. In this context, [22,23], demonstrated that tracking a small amplitude oscillatory motion of a pendulum can be made efficient by matching the (constant) stiffness of the actuators with the natural stiffness of the reference trajectory. With a similar objective in [20], the authors combined trajectory tracking with adaptation of the constant joint stiffness to its optimal value.…”
Section: Introductionmentioning
confidence: 99%
“…The optimisation of the passive system properties has also been discussed under more dynamic conditions. In this context, [22,23], demonstrated that tracking a small amplitude oscillatory motion of a pendulum can be made efficient by matching the (constant) stiffness of the actuators with the natural stiffness of the reference trajectory. With a similar objective in [20], the authors combined trajectory tracking with adaptation of the constant joint stiffness to its optimal value.…”
Section: Introductionmentioning
confidence: 99%
“…The idea is to implement joint compliance not by means of control but via adjustable intrinsically compliant joints, inspired by the unquestionably successful design of human and animal muscles. The design and control of such systems were addressed in numerous publications [45,8,44,63,53,65]. Our paper follows this general line in clearly deriving why elastic joints are necessary for human-robot soccer.…”
Section: Introducing Joint Elasticity Into the Mechanical Designmentioning
confidence: 75%
“…In WL-14 [66,67], a sophisticated nonlinear spring mechanism was used for stiffness adjustment. More recently in Lucy [63], a biped that is able to walk in the sagittal plane, approaches were made to utilize adjustable passive compliance for high energy efficiency during walking. The robot Flame [29] uses constant compliance (Series Elastic Actuation) in the hip, knee, and ankle pitch joint.…”
Section: Compliance For Walking and Runningmentioning
confidence: 99%
See 2 more Smart Citations